2016
DOI: 10.1016/j.bmcl.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium tetrathiomolybdate as a water-soluble and slow-release hydrogen sulfide donor

Abstract: Ammonium tetrathiomolybdate (TTM) was found to be a slow hydrogen sulfide (H2S) releasing agent. Its H2S generation capability in aqueous solutions was confirmed by UV-vis and fluorescence assays. TTM also showed H2S-like cytoprotective effects in hydrogen peroxide (H2O2)-induced oxidative damage in HaCaT cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…As such, it is possible to repurpose TTM as a unique inorganic complex-based H 2 S donor, analogous to the discovery of sodium nitroprusside as a widely used nitric oxide (NO) donor ( Hottinger et al, 2014 ). To this end, we studied TTM’s H 2 S-generation and relevant activities under physiological conditions ( Xu et al, 2016 ). Using a modified methylene blue method, commercially purchased TTM (99.97% purity from Sigma-Aldrich) was used to test H 2 S release in phosphate-buffered saline under pH 5, 6, 7.4, and 8.…”
Section: Donors Of Hydrogen Sulfidementioning
confidence: 99%
“…As such, it is possible to repurpose TTM as a unique inorganic complex-based H 2 S donor, analogous to the discovery of sodium nitroprusside as a widely used nitric oxide (NO) donor ( Hottinger et al, 2014 ). To this end, we studied TTM’s H 2 S-generation and relevant activities under physiological conditions ( Xu et al, 2016 ). Using a modified methylene blue method, commercially purchased TTM (99.97% purity from Sigma-Aldrich) was used to test H 2 S release in phosphate-buffered saline under pH 5, 6, 7.4, and 8.…”
Section: Donors Of Hydrogen Sulfidementioning
confidence: 99%
“…In 2016, Xu et al (2016b) reported that ammonium tetrathiomolybdate [TTM, or (NH 4 ) 2 MoS 4 ], a compound clinically used in the treatment of copper intoxication (e.g., Wilson's disease) in patients, acts as a watersoluble H 2 S donor, which probably releases H 2 S through a simple hydrolytic process, albeit with a relatively long (hours) half-life, releases more H 2 S under acidic conditions. TTM, at concentrations of 50-200 mM, exerts protective effects against oxidantinduced cell damage in vitro (Xu et al, 2016b). TTM has many different biologic effects, including inhibition of tumor cell proliferation (Chisholm et al, 2016).…”
mentioning
confidence: 99%
“…Copper chelating can exert anticancer effects through inhibiting angiogenesis (4,6,8). However, apart from copper chelating, ATTM can release H 2 S (10,11). Studies have shown that the homeostasis of H 2 S is essential in organisms (42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our lab and others have recently discovered ATTM is a pH-dependent hydrogen sulfide (H 2 S) donor (10,11). There is no doubt that the development of ATTM as a therapeutic candidate must consider ATTM being both a copper chelator and a H 2 S releaser.…”
Section: Introductionmentioning
confidence: 99%